MENGEMBANGKAN ASPEK KOGNITIF MENGENAL BILANGAN MENGGUNAKAN PROJECT BASED LEARNING DI PAUD ISLAM AL-ZAHRAH - Auliana, Nina; Darmiyati, Darmiyati (ACTION : Jurnal Inovasi Penelitian Tindakan Kelas dan Sekolah, 2025)
This research is motivated by children's low cognitive abilities in the concept of numbers. The purpose of this study is to describe teacher activities, analyze children's activities, and assess the results of children's cognitive development in recognizing numbers. This research method used a qualitative approach with Classroom Action Research (CAR) conducted over four meetings. The research setting was 13 children in Group B1 of Al-Zahrah Martapura Islamic Kindergarten. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted using qualitative descriptive techniques, described through tabulation and graphs. The results showed that teacher activities in the first meeting achieved a score of 23 (fairly good), in the second meeting achieved a score of 29 (good), in the third meeting achieved a score of 30 (good), and in the fourth meeting achieved a score of 35 (very good). Children's activity in the first meeting achieved 38%, in the second meeting achieved 46%, in the third meeting achieved 69%, and in the fourth meeting achieved 84%. Children's cognitive development in the first meeting achieved 38%, in the second meeting achieved 46%, in the third meeting achieved 77%, and in the fourth meeting achieved 85%. Based on the research results, it can be concluded that the combination of Project Based Learning, Direct Instruction, and Make a Match models in recognizing numbers can increase children's activity and development outcomes. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya kemampuan anak dalam aspek kognitif pada konsep bilangan. Tujuan penelitian ini untuk mendeskripsikan aktivitas guru, menganalisis aktivitas anak dan hasil perkembangan anak aspek kognitif dalam mengenal bilangan. Metode penelitian ini menggunakan pendekatan kualitatif dengan jenis Penelitian Tindakan Kelas(PTK) yang dilaksanakan dalam empat kali pertemuan, setting penelitian pada anak kelompok B1 TK Islam Al-Zahrah Martapura yang berjumlah 13 anak. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Analisis data dilakukan dengan teknik deskriptif kualitatif yang dijabarkan dengan tabulasi dan grafik. Hasil penelitian menunjukkan bahwa aktivitas guru pertemuan I memperoleh skor 23 kriteria “cukup baik” pertemuan II memperoleh skor 29 mencapai kriteria “baik”, pertemuan III memperoleh skor 30 “baik”, pertemuan IV mencapai skor 35 kriteria “sangat baik”. Aktivitas Anak pada pertemuan I dengan 38%, pertemuan II dengan 46%, pertemuan III dengan 69%, pertemuan IV dengan nilai skor 84%. Hasil perkembangan kognitif anak pada pertemuan I 38%, pertemuan II mencapai 46%, pertemuan III 77%, pertemuan IV 85%. Berdasarkan hasil penelitian, dapat disimpulkan bahwa kombinasi model Project Based Learning, Direct Instruction, Make a Match dalam mengenal bilangan dapat meningkatkan aktivitas, dan hasil perkembangan anak.